Hubungan Self-Efficacy dengan Kemampuan Adaptasi Akademik Mahasiswa Keperawatan Tingkat Pertama - Savitri, Nely Savrillia; Issroviatiningrum, Retno; Abdurrouf, Muh (Journal of Nursing Invention, 2025)
Background: First-year students often face various challenges when transitioning to a new academic environment. Such as increased academic demands, different social situations, and changes in learning habits. Academic flexibility is a key aspect of their success during this transition period. Self-efficacy, which is defined as an individual's belief in their ability to overcome obstacles and achieve goals, is considered to play an important role in the adaptation process. Objective: The objective of this study is to analyze the relationship between self-efficacy and academic adaptation skills in first-year nursing students. Method: This study uses a quantitative methodology with a cross-sectional approach. Data was collected using the GSE (General Self-Efficacy Scale) questionnaire, which consists of 20 questions, as well as 15 statements regarding academic adaptability. The survey involved 111 respondents using a simple random selection technique. The data was statistically analyzed using the Spearman rank test. Result: The results showed a high category of self-efficacy of 57 respondents (51.4%). Academic adaptability in the good category was 59 respondents (53.2%). The results of the statistical test obtained a p-value: 0.000 with a close relationship of 0.325 which means that there is a relationship between self-efficacy and academic adaptability in nursing students Conclusion: These results indicate that there is a relationship between Self-Efficacy and the Academic Adaptation Ability of First Year Nursing Students. Students with high self-efficacy tend to have better adaptation abilities, while students with low self-efficacy are more prone to experiencing difficulties in adjusting to the academic environment. Therefore, efforts are needed to improve the self-efficacy of new students to further support the academic adaptation process.